The IFMIF-DONES project: preliminary engineering design. (30th August 2018) - Ibarra, A.; Arbeiter, F.; Bernardi, D.; Cappelli, M.; García, A.; Heidinger, R.; Krolas, W.; Fischer, U.; Martin-Fuertes, F.; Micciché, G.; Muñoz, A.; Nitti, F.S.; et al.
Abstract: The need of a neutron source for the qualification of materials to be used in future fusion power reactors has been recognized in the European Union (EU) fusion programme for many years. The construction and exploitation of this facility is presently considered to be critical to the construction of the DEMOnstration Power Plant (DEMO). This issue has prompted the EU to launch activities for the design and engineering of the International Fusion Materials Irradiation Facility-DEMO Oriented Neutron Source (IFMIF-DONES) facility based on and taking profit of the results obtained in the Engineering Validation and Engineering Design Activities (IFMIF/EVEDA) project, presently conducted in the framework of the EU–Japan Bilateral Agreement on the Broader Approach to Fusion. These activities and research and development work for the IFMIF-DONES plant are presently taking place in the framework of a work package of the EUROfusion Consortium, in direct collaboration with the Fusion for Energy organization. The main objective of these activities is to consolidate the design and underlying technology basis in order to be ready for the start of the IFMIF-DONES construction as early as possible. In this paper, an overview and the present status of the IFMIF-DONES engineering design is presented for a generic site, making emphasis on the recent design evolution from previous phases.